2010
DOI: 10.1093/glycob/cwp203
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of immunomodulatory galectin-1 in peripheral leukocytes and adult tissues and its cytosolic organization in striated muscle

Abstract: Galectin-1 (Gal-1) is important in immune function and muscle regeneration, but its expression and localization in adult tissues and primary leukocytes remain unclear. To address this, we generated a specific monoclonal antibody against Gal-1, termed alphahGal-1, and defined a sequential peptide epitope that it recognizes, which is preserved in human and porcine Gal-1, but not in murine Gal-1. Using alphahGal-1, we found that Gal-1 is expressed in a wide range of porcine tissues, including striated muscle, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 67 publications
0
38
0
9
Order By: Relevance
“…Interestingly, in human adult tissue, highly related SPRED2 can be found in the liver and small intestine (71), where Gal-1 is also expressed (79). It is thus possible that the observations that we have made here also apply to the functioning of SPRED2.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, in human adult tissue, highly related SPRED2 can be found in the liver and small intestine (71), where Gal-1 is also expressed (79). It is thus possible that the observations that we have made here also apply to the functioning of SPRED2.…”
Section: Discussionmentioning
confidence: 63%
“…These galectins are expressed in many different cell types (including endothelial cells, platelets, and macrophages) and are also present in normal plasma. 26,27,[34][35][36] In this study, we demonstrate for the first time that FVIII can interact with at least 2 members of the galectin family (Gal-1 and Gal-3, respectively). Although a large number of putative galectin-binding partners have previously been described, our data demonstrate that the apparent affinities of Gal-1 and Gal-3 for pd-FVIII (in the range 0.12-0.47 nmol/L) are unusually high compared with those reported for other galectin-glycoprotein interactions.…”
Section: Discussionmentioning
confidence: 65%
“…48 Furthermore, Gal-1 is also expressed within EC, where it is stored together with VWF within Weibel Palade bodies and secreted after EC activation. 26,28,34 In addition, markedly elevated systemic plasma galectin levels have also been demonstrated in association with many pathological conditions, including acute inflammatory disorders and metastatic malignancy. 27,50,51 Interestingly, a series of elegant recent studies have identified novel roles for Gal-1, Gal-3, and Gal-3-binding protein in the pathogenesis of venous thrombosis.…”
Section: Downloaded Frommentioning
confidence: 99%
“…[24][25][26] This led us to hypothesize that perhaps part of the Gal-1 and Gal-3 proteins could colocalize with VWF, the majority of which is located in endothelial storage organelles, the WP bodies. To test for colocalization, we applied Duolink-PLA analysis, which detects proteins located within a radius of Ͻ40 nm.…”
Section: Gal-1 and Gal-3 Are Associated With Vwf In Endothelial Cellsmentioning
confidence: 99%
“…24 In particular, galectin-1 (Gal-1) and galectin-3 (Gal-3) are being abundantly expressed in the endothelium. [24][25][26] Moreover, glycan array analysis has revealed that both Gal-1 and Gal-3 are able to recognize carbohydrate structures that are present on the VWF molecule. 27 Here, we explored the possibility that Gal-1 and Gal-3 are able to interact with VWF.…”
mentioning
confidence: 99%